2012
DOI: 10.1016/j.jcf.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Blood basophils from cystic fibrosis patients with allergic bronchopulmonary aspergillosis are primed and hyper-responsive to stimulation by aspergillus allergens

Abstract: In CF-ABPA, blood basophils are primed and hyperresponsive to Af allergen stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 35 publications
3
59
1
Order By: Relevance
“…[15][16][17] The basophil activation test (BAT) is a novel technique that measures upregulation of CD203c upon stimulation with the specific allergen to which an individual is sensitized. 18 CD203c is an ectonucleotide pyrophosphatase/phosphodiesterase expressed on the surface of basophils, which are important effector cells in type II immune responses. 18,19 CD203c can be rapidly measured by flow cytometry and has been proposed as a diagnostic tool in atopic disease, including peanut, drug and wasp venom allergy.…”
Section: Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations
“…[15][16][17] The basophil activation test (BAT) is a novel technique that measures upregulation of CD203c upon stimulation with the specific allergen to which an individual is sensitized. 18 CD203c is an ectonucleotide pyrophosphatase/phosphodiesterase expressed on the surface of basophils, which are important effector cells in type II immune responses. 18,19 CD203c can be rapidly measured by flow cytometry and has been proposed as a diagnostic tool in atopic disease, including peanut, drug and wasp venom allergy.…”
Section: Abbreviationsmentioning
confidence: 99%
“…18 CD203c is an ectonucleotide pyrophosphatase/phosphodiesterase expressed on the surface of basophils, which are important effector cells in type II immune responses. 18,19 CD203c can be rapidly measured by flow cytometry and has been proposed as a diagnostic tool in atopic disease, including peanut, drug and wasp venom allergy. [20][21][22] It has been shown that basophils are primed and hyper-responsive to Af allergen stimulation in CF-ABPA.…”
Section: Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, subsets of cells identified by flow cytometry are frequently compared to find such differences. Specifically, comparisons between a disease sample and control, different genetically modified organisms, or samples that have undergone stimulations provide fundamental information [20,21,22]. Therefore, it is important to have appropriate methods to characterize these differences in a quantitative and useful way.…”
Section: Discussionmentioning
confidence: 99%